2016
DOI: 10.3389/fonc.2016.00036
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Gynecological Malignancies

Abstract: ObjectivesHealth disparities and inequalities in access to care among different socioeconomic, ethnic, and racial groups have been well documented in the U.S. healthcare system. In this review, we aimed to provide an overview of barriers to care contributing to health disparities in gynecological oncology management and to describe site-specific disparities in gynecologic care for endometrial, ovarian, and cervical cancer.MethodsWe performed a literature review of peer-reviewed academic and governmental public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 81 publications
3
81
0
Order By: Relevance
“…However, African American women are more likely to be diagnosed with advanced disease compared to Caucasians [19,20,21,22]. A Texas study observed that 20% of Hispanic women presenting with stage IV disease had never had a Pap smear, compared to 3% of women presenting at a similar disease stage [20,22,23].…”
Section: Screening Uptake and Disease Stagementioning
confidence: 99%
See 3 more Smart Citations
“…However, African American women are more likely to be diagnosed with advanced disease compared to Caucasians [19,20,21,22]. A Texas study observed that 20% of Hispanic women presenting with stage IV disease had never had a Pap smear, compared to 3% of women presenting at a similar disease stage [20,22,23].…”
Section: Screening Uptake and Disease Stagementioning
confidence: 99%
“…In the most recent analysis of cervical cancer screening uptake by the Centers for Disease Control, 81% of women in the USA had undergone cytological screening within the last 3 years, and this rate was slightly higher in African American women, while rates were significantly lower among Asian and Hispanic women [19,20]. However, African American women are more likely to be diagnosed with advanced disease compared to Caucasians [19,20,21,22].…”
Section: Screening Uptake and Disease Stagementioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have explored racial/ethnic treatment and survival disparities in endometrial cancer [2024]. Black women are less likely to receive appropriate staging and guideline-concordant treatment and have poorer survival than their white peers [2024]. However, there is a paucity of research evaluating disparities between rural and urban populations.…”
Section: Introductionmentioning
confidence: 99%